Study of Design Modification Effects through Performance Analysis of a Legacy Gas Turbine Engine - Gouda,Gantayata (2020)
ABSTRACT: Modifications to the critical parameters, such as the exhaust nozzle area, are sometimes done during maintenance of aircraft engines. These modifications are done either to increase the design thrust or to compensate for the reduction of thrust due to leakage in the variable area jet nozzle. There is a trade-off between several performance parameters when such critical parameters are changed during maintenance. A tuned aerothermodynamic simulation model that agrees well with the experimental data from the original engine is required to study the effect of these changes. In the present work, a multipoint map scaling approach and a parameter estimation method are used to develop a simulation model that agrees well with the experimental data from the original turbojet engine. The design modifications are then incorporated in the model, and the effect of the modification on the various performance parameters is studied. The effect of leakage in the nozzle flaps and the corresponding reduction required in the nozzle throat area are calculated. It is shown that the tuned model developed with experimental testbed data enables the identification of ancillary effects of a change in a design parameter, such as the nozzle throat area.